Computer model for agricultural holdings: Useful tool in the evaluation and implementation of a high performance management - Rozi Liliana Berevoianu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
Development continuous information models in the agricultural sector, as the data collection methods and modern and efficient processing of the system of economic and financial indicators and assessing risks in agricultural holdings may have a positive impact on increasing the competitiveness of production processes, is a viable solution for streamlining activities in agriculture. From this point of view, at the level of an agricultural holding, the data model can become a real component in the process of management. The main aim is to improve the decision-making process from the farm and the provision of information management systems necessary to adapt to a society directed toward knowledge and access to information.
Keywords: 330; computer model; agricultural management; economic and financial indicators; economic risk